INFORMATION USE PATTERN OF CIVIL AND MECHANICAL ENGINEERING FACULTY OF UNIVERSITY COLLEGE OF ENGINEERING AUTONOMOUS JNTUK KAKINADA: A STUDY - Naick, Doraswamy; Rao Bavisetti, Venkateswara (International Journal of Research -GRANTHAALAYAH, 2018)
This Article to express the role of Web based information services of Civil and Mechanical Engineering faculty of University College of Engineering Autonomous Jawaharlal Nehru Technological University, Kakinada the Researcher has used the survey method to collect data from the University College of Engineering Autonomous faculty especially Regular Library users. The faculty are processed technically and tabulated as to the variables of the concerned topic of online resources.